Association between CSF biomarkers of Alzheimer's disease and neuropsychiatric symptoms: Mayo Clinic Study of Aging - Krell-Roesch, Janina; Rakusa, Martin; Syrjanen, Jeremy A; van Harten, Argonde C; Lowe, Val J; Jack, Clifford R; Kremers, Walter K; Knopman, David S; Stokin, Gorazd B; Petersen, Ronald C; Vassilaki, Maria; Geda, Yonas E (Alzheimer's & dementia, 2023)
INTRODUCTION: We examined the association between cerebrospinal fluid (CSF)-derived biomarkers of Alzheimer's disease and neuropsychiatric symptoms (NPS) in older non-demented adults. METHODS: We included 784 persons (699 cognitively unimpaired, 85 with mild cognitive impairment) aged ≥ 50 years who underwent CSF amyloid beta (Aβ42), hyperphosphorylated tau 181 (p-tau), and total tau (t-tau) as well as NPS assessment using Beck Depression and Anxiety Inventories (BDI-II, BAI), and Neuropsychiatric Inventory Questionnaire (NPI-Q). RESULTS: Lower CSF Aβ42, and higher t-tau/Aβ42 and p-tau/Aβ42 ratios were associated with BDI-II and BAI total scores, clinical depression (BDI-II ≥ 13), and clinical anxiety (BAI ≥ 10), as well as NPI-Q-assessed anxiety, apathy, and nighttime behavior. DISCUSSION: CSF Aβ42, t-tau/Aβ42, and p-tau/Aβ42 ratios were associated with NPS in community-dwelling individuals free of dementia. If confirmed by a longitudinal cohort study, the findings have clinical relevance of taking into account the NPS status of individuals with abnormal CSF biomarkers.
Keywords: CSF total tau; Cognitive Dysfunction; biologické markery; Amyloid beta-Peptides; tau Proteins; Biomarkers; Aging; longitudinální studie; neuropsychiatric symptoms; lidé; amyloidní beta-protein; CSF phosphorylated tau; cerebrospinal fluid biomarkers; peptidové fragmenty; CSF amyloid beta 42; Alzheimer's disease; Peptide Fragments; non-demented; Aged; Alzheimer Disease; stárnutí; kognitivní dysfunkce; Alzheimerova nemoc; senioři; proteiny tau; Longitudinal Studies; Humans